IMPLEMENTASI PAKET TEKNOLOGI PENGOLAH KEDELAI BAHAN BAKU TEMPE DAN PENATAAN MANAJEMEN BERBASIS DIGITAL PADA KOPTTI SUMBER REJEKI SIDOARJO - Yunus, Yunus; Ridlwan, Ahmad Ajib; Ramis, Irfan; Azizah, Wafiq; Fathoni , Rizki Dwi; Amin, Gempar Yanuar Al (Jurnal Abdimas Bina Bangsa, 2025)
Soybeans are a type of legume that is usually used in Indonesian culture and cuisine, especially as a base for tempe. Tempe is fermented soybeans made traditionally. The manufacturing process includes peeling the soybeans, soaking, steaming and fermenting the soybeans with the fungus Rhizopus oligosporus. Tempe is also a popular food in Indonesia, so many businesses produce tempeh. One of them is the Indonesian Tofu and Tempe Producers Cooperative (KOPTTI Sumber Rejeki) with the Cooperative Chairman Mr. Suyanto, a cooperative that oversees 33 MSMEs that produce tempeh in Kedungcangkring, Sidoarjo. This cooperative, which houses 33 tempe producing UMKM, is experiencing problems ranging from management that is not well organized, limited production capacity, and unhygienic production processes. The aim of the activity is to resolve production process problems, namely low hygiene and production results in washing, and synchronization of soybean epidermis as well as resolving problems in management, namely weak financial management and productivity. The methods applied in this service activity start from finding and determining priority problems, designing soybean machines, carrying out manufacturing processes, implementing washing machines and soybean epidermis separating machines, mentoring and monitoring. The results obtained from this service activity were through the implementation of the soybean processing technology package for tempeh raw materials, namely increasing production capacity when the soybean washing process started from 100kg to 180kg and then when the breaking process started from 80kg to 300kg. Production quality has also increased due to machines made from food grade 304 stainless steel so that the quality and quantity of productivity at partners has increased. The implementation management team provides assistance and training starting from structuring production, structuring workers and structuring finances.